Russkie skazki : russkie narodnye skazki - Tolstoy, Leo, graf, 1828-1910; Bulatov, M. A. (Mikhail Aleksandrovich), 1913-1963; Sokolʹskai͡a, T. G.; Sokolʹskiĭ, G. M. (Chitaem sami (Omega (Firm)), 2005)
A collection of Russian tales.